CD24 gene exon 2 dimorphism does not affect disease susceptibility in Japanese sarcoidosis patients - Tanizawa, K.; Handa, T.; Nagai, et al., S. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Background: CD24 proteins are expressed on several inflammatory cells, and play an important role for the T-cell activation. Objectives: The aim of this study is to investigate the relationship of a CD24 gene polymorphism to disease susceptibility or clinical findings including bronchoalveolar lavage (BAL) cell profiles in Japanese sarcoidosis patients.Methods: A previously reported functional single nucleotide polymorphism (SNP) of CD24 gene exon 2 was examined in 186 Japanese sarcoidosis patients and 146 sex and age-matched healthy controls using restriction fragment length polymorphism method.The distribution of genotypes was compared between the two groups. The association between genotypes or alleles and clinical features or BAL cell profiles was also examined. Results: There were no significant differences in the distribution of genotypes or allele frequencies between sarcoidosis and controls.There were also no significant differences in clinical features or BAL cell profiles among patients with different genotypes of CD24. Conclusions: There was no relationship between a CD24 exon 2 SNP and disease susceptibility or clinical findings in Japanese sarcoidosis patients.